TNF-α Antagonism with Etanercept Decreases Glucose and Increases the Proportion of High Molecular Weight Adiponectin in Obese Subjects with Features of the Metabolic Syndrome - Stanley, Takara L.; Zanni, Markella V.; Johnsen, Stine; Rasheed, Sarah; Makimura, Hideo; Lee, Hang; Khor, Victor K.; Ahima, Rexford S.; Grinspoon, Steven K. (The journal of clinical endocrinology and metabolism, 2011)
Context and Objective: Obesity is associated with activation of the TNF-α system, increased inflammatory markers, and insulin resistance. Although studies in rodents suggest that attenuation of TNF activity improves glucose homeostasis, the effect of prolonged inhibition of TNF-α with etanercept on inflammation and glucose homeostasis in a human model of obesity is not known. Design and Participants: Forty obese subjects with features of metabolic syndrome were randomized to etanercept or placebo, 50 mg twice weekly for 3 months, followed by 50 mg once weekly for 3 months. Outcome Measures: Subjects underwent oral glucose tolerance testing and measurement of serum inflammatory biomarkers and adipokines. Subcutaneous fat biopsy was performed in a subset for measurement of adipokine and TNF-α mRNA expression. Results: Visceral adiposity was significantly associated with serum concentrations of TNF receptor 1 (TNFR1), TNFR2, and vascular cell adhesion molecule-1 and adipose tissue expression of TNF-α and SOCS-3 (all P < 0.05). Insulin resistance as assessed by homeostasis model assessment was significantly associated with TNFR1, C-reactive protein, IL-6, and soluble intracellular adhesion molecule-1 (sICAM-1) (all P < 0.05). Etanercept significantly improved fasting glucose (treatment effect vs. placebo over 6 months, −10.8 ± 4.4%, P = 0.02). Etanercept also increased the ratio of high molecular weight adiponectin to total adiponectin (+22.1 ± 9.2% vs. placebo, P = 0.02), and decreased levels of sICAM-1 (−11 ± 2% vs. placebo, P < 0.0001). In contrast, body composition, lipids, C-reactive protein, and IL-6 were unchanged after 6 months. Conclusions: Prolonged therapy with etanercept improved fasting glucose, increased the ratio of high molecular weight to total adiponectin, and decreased sICAM-1 in obese subjects with abnormal glucose homeostasis and significant subclinical inflammation.